Датировка и происхождение пальчатых фибул боспорского некрополя раннесредневекового периода - Засецкая, И.П. (Материалы по археологии, истории и этнографии Таврии, 1998)
A new detailed typology of radiate-headed broochesfinger-shaped fibulas) is given in this article. They are classified according to 27 characteristics. As the result of their correlation four groups are formed.